Eating‐ and oral health‐related quality of life in patients under fixed orthodontic treatment - Yasamin Babaee Hemmati; Arastoo Mirmoayed; Mohammad Ebrahim Ghaffari; Mehran Falahchai (Wiley, 2022)
Abstract Objective The eating problems and changes in the diet and dietary intake of patients under orthodontic treatment are of great importance, and the available studies on this topic are mostly qualitative. Thus, this study aimed to assess the oral health‐related quality of life (OHRQoL) and the eating‐related quality of life (ERQoL) of patients under fixed orthodontic treatment. Materials and Methods This prospective study evaluated 105 patients (65 males, 40 females) with a mean age of 26 ± 1.1 years, who required fixed orthodontic treatment. All participants filled out the Oral Health Impact Profile‐14 (OHIP‐14) questionnaire before treatment (T0), and at 1 (T1), 3 (T2), and 6 (T3) months after treatment, and the ERQoL questionnaire at 1 (T1), 3 (T2), and 6 (T3) months after treatment. Data were analyzed using repeated measures analysis of variance with Greenhouse-Geisser and Huynh‐Feldt corrections and Bonferroni test for pairwise comparisons (α = .05). Results The OHIP‐14 total score increased at T1 and decreased at T2 and T3, with significant differences between all four time points (p < .001). The ERQoL total score decreased over time, and significant differences were noted between all three time points (p < .001). No significant difference existed in OHRQoL or ERQoL with regard to gender at any time point (p > .05). Conclusion The reduction in OHRQoL due to fixed orthodontic treatment was temporary and improved over time. The eating problems also decreased with time.